Co‐occurrence of CDKN2A/B and IFN‐I homozygous deletions correlates with an immunosuppressive phenotype and poor prognosis in lung adenocarcinoma - Yuan Peng (Molecular Oncology, 2022)
Homozygous deletion (HD) of CDKN2A and CDKN2B (CDKN2A/BHD) is the most frequent copy‐number variation (CNV) in lung adenocarcinoma (LUAD). CDKN2A/BHD has been associated with poor outcomes in LUAD; however, the mechanisms of its prognostic effect remain unknown. We analyzed genome, transcriptome, and clinical data from 517 patients with LUAD from the Cancer Genome Atlas (TCGA) and from 788 primary LUAD tumor and matched control samples from the MSK‐IMPACT clinical cohort. CDKN2A/BHD was present in 19.1% of the TCGA‐LUAD cohort and in 5.7% of the MSK‐IMPACT cohort. CDKN2A/BHD patients had shorter disease‐free survival and overall survival compared with CDKN2A/BWT individuals in both cohorts. Differences in clinical features did not influence the outcomes in the CDKN2A/BHD population. Mutation analyses showed that overall tumor mutational burden and mutations in classical drivers such as EGFR and RB1 were not associated with CDKN2A/BHD. In contrast, homozygous deletion of type I interferons (IFN‐IHD) frequently co‐occurred with CDKN2A/BHD. CDKN2A/B and IFN‐I are co‐located in the same p21.3 region of chromosome 9. The co‐occurrence of CDKN2A/BHD and IFN‐IHD was not related to whole‐genome doubling, chromosome instability, or aneuploidy. Patients with co‐occurring CDKN2A/BHD and IFN‐IHD had shorter disease‐free survival and overall survival compared with CDKN2A/BWT patients. CDKN2A/BHDIFN‐IHD had downregulated several key immune response pathways, suggesting that poor prognosis in CDKN2A/BHD LUAD could potentially be attributed to an immunosuppressive tumor microenvironment as a result of IFN‐I depletion.